Analisis Potensi Likuefaksi Dengan Alat Swedish Weight Sounding di Desa Tompe Kecamatan Sirenja Kabupaten Donggala - Setiawan, H.; Sutrisno, M.; Hasanah, Y.; Rizal, A.; Kurniawan, A.; Qhalbi, A.N.; Gayatri, S. (Tadulako University, 2025)
In 2018 in Indonesia there has been an earthquake of 7.4 on the richter scale. The epicenter was on land around Sirenja district, Donggala regency, Central Sulawesi. The impact in some areas there is liquefaction of these areas, namely Petobo village and Balaroa village and also subsidence in Tompe Village this study aims to determine whether the soil in segment II of Tompe village has the potential for liquefaction based on the results of Cyclic Stress Ratio (CSR) & Cyclic Resistance Ratio (CRR) analysis and based on the results of Tsuchida grain distribution graph. Samples in this study amounted to 10 points by field testing using Swedish weight sounding tool to obtain the value of Nsw (n/m) correlated to the N-SPT data and analyzed by the CSR & CRR equation to obtain the value of the safety factor (FS). The results obtained with the range of FS values are for the potential 0.13 – 0.98 and not potential 1.06 – 1.72 and based on the results of grading the grain to get the value for the potential 70.31% - 95.87% and not the potential 0.39% - 6.62% from the results of the 2 methods it is concluded that Tompe village based on the value of FS 50% has the potential for liquefaction and based on the Tsuchida graph 85.78% has the potential for liquefaction.